EFL Teachers’ Strategies in Teaching Four Language Skills during Online Learning - Hardina D. Ni’mah; Utami Widiati (Jurnal Pendidikan Humaniora, 2021)
Abstract: Education has changed intensely whereby teaching is undertaken remotely and on digital platforms. Challenges risen among the teachers to face the shifting mode of teaching from conventional to online activities. Hence, selecting the right strategy is needed to support the teaching activities. This research employed a multiple case study to determine how EFL teachers implemented strategies in teaching four language skills (speaking, listening, reading, and writing) during online learning. Three tools were applied in this research: Field Note, Interview and Archival Record Documents.Keywords: teaching strategy, language skill, online learningAbstrak: Pendidikan telah berubah secara dramatis dimana pengajaran dilakukan dari jarak jauh dan pada platform digital. Tantangan muncul di kalangan guru untuk menghadapi pergeseran mode pengajaran dari konvensional ke kegiatan daring. Oleh karena itu, pemilihan strategi yang tepat sangat diperlukan untuk mendukung kegiatan pengajaran. Penelitian ini menggunakan beberapa studi kasus untuk menentukan bagaimana guru EFL menerapkan strategi dalam mengajar empat keterampilan bahasa (berbicara, mendengarkan, membaca, dan menulis) selama pembelajaran daring. Tiga alat yang digunakan dalam penelitian ini: Catatan Lapangan, Wawancara dan Dokumen Arsip.Kata kunci: strategi pengajaran, keterampilan bahasa, pembelajaran online